6-12 years old Children´s Recreation in the Río Guaso Community - Ernys Bess-Castillo (Universidad de Guantánamo, 2012)
This investigating work has its bases in the proposal of a system of recreational sports actions to increase the power of the recreation of children of 6 to 12 years old in the community Río Guaso, due to insufficiency in the recreational activities at the locality, which is why we proposed the design of a system of recreational and sportive activities that favor these children's recreation. Different fact-finding methods were used for this proposal. It was checked that recreation becomes stronger with the implementation of this system of activities, obtaining better results that demonstrated the feasibility of our proposal.